Behavioral Patterns in Special Education. Good Teaching Practices - Rodríguez-Dorta, Manuela; Borges, África (Frontiers in Psychology, 2017)
Providing quality education means to respond to the diversity in the classroom. The teacher is a key figure in responding to the various educational needs presented by students. Specifically, special education professionals are of great importance as they are the ones who lend their support to regular classroom teachers and offer specialized educational assistance to students who require it. Therefore, special education is different from what takes place in the regular classroom, demanding greater commitment by the teacher. There are certain behaviors, considered good teaching practices, which teachers have always been connected with to achieve good teaching and good learning. To ensure that these teachers are carrying out their educational work properly it is necessary to evaluate. This means having appropriate instruments. The Observational Protocol for Teaching Functions in Primary School and Special Education (PROFUNDO-EPE, v.3., in Spanish) allows to capture behaviors from these professionals and behavioral patterns that correspond to good teaching practices. In this study the behavior of two special education teachers who carry out their educational work in different contexts is evaluated. It reveals that teachers who were analyzed adapt their behavior depending on the context in which they carry out their educational work, providing the most appropriate response to the needs presented by students and showing good teaching practices.